Stormwater Pond Management: What You Need to Know about Aeration - Samantha T. Howley; Steven P. Hohman; Alexander J. Reisinger (EDIS)
This new 6-page document is intended to provide Floridians and their communities with information on a specific management practice in stormwater ponds: the use of fountains and other aeration approaches. These practices may provide opportunities both to improve water quality within the pond and protect downstream water quality. Specifically, this document gives basic information on fountains and the pros and cons of fountain installation and use. In addition, we provide information for pond managers or community decision makers on how to best manage ponds for effective pollutant removal in the pond and downstream water quality protection. Written by Samantha T. Howley, Steven P. Hohman, and Alexander J. Reisinger, and published by the UF/IFAS Department of Soil and Water Sciences. https://edis.ifas.ufl.edu/ss695